2020
DOI: 10.1111/2041-210x.13522
|View full text |Cite
|
Sign up to set email alerts
|

A spatial capture–recapture model to estimate call rate and population density from passive acoustic surveys

Abstract: Spatial capture–recapture (SCR) models are commonly used to estimate animal population density from detections and subsequent redetections of individuals across space. In particular, acoustic SCR models deal with detections of animal vocalisations across an array of acoustic detectors. Previously published acoustic SCR methods either estimate call density (calls per unit space per unit time) rather than animal density itself, require an independently estimated call rate to estimate animal density, or discard d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 38 publications
(85 reference statements)
0
20
0
Order By: Relevance
“…ARUs are being increasingly used to obtain estimates of key population parameters such as occupancy, abundance, call rate and density (Marques et al., 2013; Pérez‐Granados & Traba, 2021; Sebastián‐González et al., 2018; Stevenson et al., 2021). Nevertheless, our simple occupancy case study demonstrated how impactful the choice of method to analyze acoustic data can be on those estimates.…”
Section: Discussionmentioning
confidence: 99%
“…ARUs are being increasingly used to obtain estimates of key population parameters such as occupancy, abundance, call rate and density (Marques et al., 2013; Pérez‐Granados & Traba, 2021; Sebastián‐González et al., 2018; Stevenson et al., 2021). Nevertheless, our simple occupancy case study demonstrated how impactful the choice of method to analyze acoustic data can be on those estimates.…”
Section: Discussionmentioning
confidence: 99%
“…SCR has shown to integrate biotic and abiotic observations at large spatio‐temporal scales to investigate complex population‐level processes. Methodological developments, such as data integration (Chandler & Clark, 2014), continuous time detection (Borchers et al, 2014), noncircular home ranges (Sutherland et al, 2015), density‐dependent home ranges (Efford et al, 2016), and passive acoustic SCR (Stevenson et al, 2021) extend our ability to incorporate complex data structures and hierarchical relationships scaled from the individual to population and species level. Availability of software packages and comprehensive support by the community of users and developers has helped researchers formulate SCR models according to their specific ecological state and observation processes of interest.…”
Section: Discussionmentioning
confidence: 99%
“…Standard SCR relies on animals moving between detection locations and hence typically requires multiple capture occasions, while in ASCR the sound travels almost instantaneously from its source and hence can be detected on multiple sensors in a single occasion. Estimation is of cue spatial density; to convert to animal density an estimate of average cue production rate is required (Marques et al, 2013;Stevenson et al, 2021). As well as the location of detection, additional information is often available about the location of the vocalisation, e.g., the bearing, received sound level or time of arrival on multiple sensors.…”
Section: Introductionmentioning
confidence: 99%